(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The purpose of this paper is to investigate the effect of stone crushed dust on the specific properties of fresh and toughened concrete (M25). These experimental trails for fresh and toughened concrete properties for M-25 grade are investigated and the results are compared to normal concrete. It has the potential to be used in concrete as a partial replacement for natural river sand. The utilization of stone dust in concrete not as it were moves forward concrete quality but moreover makes a difference to protect characteristic waterway sand for future generations. An exploratory program was carried out within the current ponder to explore the workability and compressive strength of concrete made utilizing stone clean as a fractional substitution of fine of concrete made using stone dust as a partial replacement of fine aggregate in the range of 10% - 100%. M25 grade for referral concrete, a concrete grade was designed using OPC. Workability and compressive quality were decided at different substitution levels of fine total versus referral concrete, with compressive quality deciding the ideal substitution level. In comparison to all other replacement levels, the results showed that replacing 60% of fine aggregate with stone dust allows for the production of concrete with the highest compressive strength.